Pay it forward: Can perceived behavioral control to pass on scholarship aid be predicted by various narcissism? - Aisa, Adiska Uswa; Abraham, Juneman; Pramastyaningtyas, Angela Dyah Ari (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
One way of making scholarships sustainable is to continue the “chain of kindness.” However, relatively few studies have examined the psychological predictors involved in making a scholarship recipient feel that “pay it forward” is under their control. This study aimed to determine the predictions of four types of narcissism on Perceived Behavioral Control (PBC) in continuing scholarship. The instruments used comprised psychological scales measuring PBC, which were constructed by the authors, and some types of narcissism, i.e. the Communal Narcissism Inventory (CNI), Brief-Pathological Narcissism Inventory (B-PNI), and the Narcissistic Personality Inventory-16 (NPI). Data were obtained by convenience sampling from 212 Indonesian scholarship recipients and analyzed with multiple linear regression (predictive correlational design). The results showed that the regression model had statistical significance (F(4, 211)= 15.452, p = .000, R2 = 23%). A notable result was that communal narcissism predicted PBC in a positive direction. Narcissism often has negative connotations; however, the results contribute by showing that there is also a “bright side” of narcissism.